Chronicle of international labor jurisprudence 2020 - Arias Domínguez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In the reference period, no resolutions have been issued by the Committee on Freedom of Association that affect the Spanish state. Nor have significant pronouncements of the ECHR been issued on labor or social protection matters. We do have, as is usual, numerous resolutions of the CJEU of social content that affect the Spanish state and that we will now expose, ordering them, as is traditional, by strictly chronological criteria. The STJUE of January 22, 2019 [C-177/18] Baldomero Martín and Madrid City Council, addresses the eventual discrimination suffered by the interim official who does not receive compensation at the end of his service relationship, unlike what happens with the personnel hired under the labor regime. The ATJUE of February 4, 2020 [C-811/18] KA and INSS and TGSS, questions the exclusion of men from the maternity supplement that is incorporated into the LGSS to supplement the pensions of women who have been mothers. The ATJUE of March 5, 2020 [C-861/19] LJ and INSS also questioned the exclusion of men from the maternity supplement. The STJUE of March 19, 2020 [C-103/18 and C-429/18] Sánchez Ruiz and Fernández Álvarez and others v. Madrid Health Service is one of the many resolutions that analyze irregular temporary hiring by public administrations, in this case analyzing the perspective of the renewal of successive relationships of fixed-term services. The AJEU of June 4, 2020 [C-588/18] Fetico y otros v. DIA and others, deals with the dies a quo and the calculation of the terms of paid work leave. The STJUE of September 16, 2020 [C-462/19] National Markets and Competition Commission c. The National Association of Stevedoring Companies and Ship Consignees and others, deems the question raised inadmissible. It serves to mark the limits and borders of the preliminary question and the active legitimation of its approach, prohibited to administrative bodies, even if they effectively resolve conflicts of interest between parties. The STJUE of November 11, 2020 [C-300/19] UQ and Marclean Technologies v. The Public Prosecutor’s Office and the Salary Guarantee Fund analyzes the reference period that must be taken into consideration when collective redundancies are carried out.